Research on the process of naphtha hydrocracking to chemical materials - Kui Zhang; Zhihai Hu; Liang Ren; Hong Nie; Guangle Zhao; Yuanbing Xi; Chunlu Wang (Carbon Resources Conversion)
To systematically study the conversion process of paraffin, cycloalkane, and aromatic on ZSM-5 molecular sieve in naphtha hydrocracking, a series of related experiments were carried out based on the prepared hydrocracking catalyst, Catalyst-HC. Ni and ZSM-5 molecular sieve were selected as the hydrogenation active component and the cracking component of Catalyst-HC, respectively. The results obtained through this work indicate that on ZSM-5 molecular sieve, the paraffin and cycloalkane in naphtha are mainly convertible hydrocarbons. The higher the content of convertible hydrocarbons in naphtha, the easier it is for the conversion reaction to occur. As C5+ conversion rate rises, the yields of paraffin and cycloalkane decline, and the yields of aromatic and aromatic-carbon in product-naphtha remain almost unchanged. The aromatic-average carbon-number (CN) in product-naphtha changes very little, decreasing from 8.3 to 8.2. This means that almost no aromatic undergoes the saturation reaction or conversion reaction on Catalyst-HC. Due to the small pore size of ZSM-5, C5+ i-paraffin has a lower conversion rate and a higher average CN compared to C5+ n-paraffin. Meanwhile, as C5+ conversion rate gradually rises from 0 to 23 %, the average CN drop-values of C5+ n-paraffin and C5+ i-paraffin are 1.3 and 0.14, respectively. C5-ring cycloalkane-ring-carbon (C5-ring CRC) is more likely undergoing ring-opening (RO) reaction than that of C6-ring cycloalkane-ring-carbon (C6-ring CRC). The conversion rate of C5-C7 cycloalkane is higher than that of C8+ cycloalkane, and the former bears a higher jump-value compared to the latter with the increase of C5+ conversion rate. Unlike paraffin and aromatic, the average CN of cycloalkane gradually rises with the increase of C5+ conversion rate.